IMPROVING SPEAKING SKILL BY USING ROLE PLAY FOR TEENAGER - Vibry Andina Nurhidayah (Raheema, 2020)
ABSTRACT This study revealed the teaching speaking by using role play. This is classroom action research. The subjects under the study was the students of class VIIA in academic year 2017/2018, it consist of 31 students. This is done in 2 cycles. The research result is the speaking ability in VII A MTs Mathla’ul Anwar Pontianak had an improvement. It could be seen with the mean score in cycle 1 achive 57.60 % and in cycle 2 had achive 73.54%. Keyword: Speaking, Role Play, Teenager, ABSTRAK Studi ini mengungkapkan pengajaran berbicara dengan menggunakan permainan peran. Ini adalah penelitian tindakan kelas. Subjek penelitian adalah siswa kelas VIIA pada tahun akademik 2017/2018, terdiri dari 31 siswa. Hal ini dilakukan dalam 2 siklus. Hasil penelitian adalah kemampuan berbicara dalam VII A MTs Mathla'ul Anwar Pontianak mengalami perbaikan. Hal ini dapat dilihat dengan skor rata dalam siklus 1 mencapai 57,60% dan dalam siklus 2 telah mencapai 73,54%. Kata kunci: berbicara, role play, remaja,